2021
DOI: 10.1186/s12889-020-09974-x
|View full text |Cite
|
Sign up to set email alerts
|

Sports activities of 60 above Hungarian elderly-explaining and predicting impact of exercise on health

Abstract: Background The proportion of elderly is on the rise both in Europe and in Hungary. The challenge is to increase the number of years spent in good health as well as to improve quality of life of those 60 years and above. This study focuses on the impact of physical activity on this age group. Methods A nationally representative sample of 2000 respondents were surveyed in an age range of 15–74. Our data concerns those being 60–74 years of age. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…In this regard, it should be noted that there are no studies that address the effect that co-living has on the types of sports practiced. However, in a study carried out with people aged 60 to 74 years, it was found that the majority of those who did not perform any physical-sports activity had a negative culture towards the practice of sports and also practiced low-intensity sports [40]. Another study of 7759 people aged from 65 to 84 found that compared to not exercising, exercising alone or with others was much better for good physical and mental function; however, in comparison to this study, our findings show differences according to the different sport modalities and their type of company.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be noted that there are no studies that address the effect that co-living has on the types of sports practiced. However, in a study carried out with people aged 60 to 74 years, it was found that the majority of those who did not perform any physical-sports activity had a negative culture towards the practice of sports and also practiced low-intensity sports [40]. Another study of 7759 people aged from 65 to 84 found that compared to not exercising, exercising alone or with others was much better for good physical and mental function; however, in comparison to this study, our findings show differences according to the different sport modalities and their type of company.…”
Section: Discussionmentioning
confidence: 99%
“…Tudományos kutatások megannyi szemszögből taglalják az időskorúak fizikai aktivitásának kérdését. Közös alapelv, hogy az aktív mozgásos életmód pozitívan befolyásolja az időskorúak életminőségét és életkilátásait (LAMPEK et al, 2021;IVÁN, 2002;PAWLOWSKI et al, 2011;TAYLOR -FINELY, 2020). A koronavírus-járvány kitörése után bevezetett korlátozó intézkedések érvénybe lépése nagymértékben csökkentette embertársainkkal való kapcsolattartás lehetőségeit (PETERS et al, 2020).…”
Section: Elméleti Háttérunclassified
“…Az emberek egyre határozottabban igényeket fogalmaznak meg egészségüket tekintve, sőt ez nem csak testi vonatkozásban fogalmazódik meg, hanem a lelki, szellemi jellemzők vonatkozásában is. Mindezek egy soha ki nem elégíthető, állandóan bővülő igényhalmazt eredményeznek, vagyis az emberek elvárása ezen a területen szinte határtalan (Lampek et al, 2014). Megállapítható tehát, hogy az egyének egészségszemlélete az egészséggel, betegséggel és jólléttel kapcsolatos ismeretét és tájékozottságtát mutatja.…”
Section: Az Egészségmagatartás Alkotóelemeiunclassified